2008
DOI: 10.1152/ajpheart.00319.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy in high-fat diet-induced obesity: role of suppression of forkhead transcription factor and atrophy gene transcription

Abstract: Cellular hypertrophy is regulated by coordinated pro- and antigrowth machineries. Foxo transcription factors initiate an atrophy-related gene program to counter hypertrophic growth. This study was designed to evaluate the role of Akt, the forkhead transcription factor Foxo3a, and atrophy genes muscle-specific RING finger (MuRF)-1 and atrogin-1 in cardiac hypertrophy and contractile dysfunction associated with high-fat diet-induced obesity. Mice were fed a low- or high-fat diet for 6 mo along with a food-restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 52 publications
7
90
0
1
Order By: Relevance
“…In fact, in a previous study, some investigators found myocardial contractile dysfunction in rats fed with high-fat diet-induced obesity for 6 months. 20 The increase in total distance running and peak oxygen consumption shows the effectiveness of our exercise training paradigm. Interestingly, the increase in total distance running was proportionally greater than the increase in peak oxygen consumption in exercise-trained rats.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In fact, in a previous study, some investigators found myocardial contractile dysfunction in rats fed with high-fat diet-induced obesity for 6 months. 20 The increase in total distance running and peak oxygen consumption shows the effectiveness of our exercise training paradigm. Interestingly, the increase in total distance running was proportionally greater than the increase in peak oxygen consumption in exercise-trained rats.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies show that obesity causes cardiac dysfunction and decrease in SERCA2 activity and phosphorylation of PLN. 5,19 More recently, Fang et al 20 elegantly demonstrated that cardiac dysfunction and impairment in intracellular Ca 2ϩ handling in mice are attributed to high-fat diet-induced obesity rather than high-fat diet intake without weight gain. The present study extends these findings showing that chronic high-fat and sucrose diet-induced obesity provokes a reduction in left ventricular systolic function and phospho-Thr 17 -PLN and phosphoSer 2808 -RyR protein expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore examined what effect weight loss had on the hypertrophic signaling pathway in the hearts of obese heart failure mice. Inhibition of FOXO and the decrease in downstream atrogin-1 expression have been implicated in HF-dietinduced cardiac hypertrophy (59). On the other hand, activation of FOXO has been shown to promote cardiac (60) and skeletal muscle atrophy (61).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showing that the E3-ligases are critical for maintenance of heart mass further support the concept that the Ub pathway plays an important role in heart physiology. [10][11][12] The Ub pathway has also been implicated in various conditions affecting the heart such as diabetes, dilated cardiomyopathy, oxidative stress, and ischemia-reperfusion injury. 8,[13][14][15] Animal studies suggest that cardiac muscle is more resistant to the catabolic effects of glucocorticoids compared to skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%